Adverse events in faecal microbiota transplant: a review of the literature. Issue 2 (February 2016) - Baxter, M.; Colville, A.
Summary: Background: Faecal microbiota transplant (FMT) is the infusion of donor faeces into the gut with the aim of improving microbial diversity. The procedure has gained significant interest recently in the treatment of recurrent Clostridium difficile infection (CDI). The literature is currently dominated by small case series and isolated case reports. There is no standardization of methods and recording of outcomes. Aim: To present the adverse events that have been associated with the use of FMT, as reported in the English literature to date. Methods: A database search of Medline and Embase identified publications where FMT has been administered. Review articles were excluded. In total, 109 publications were identified that described the use of FMT in 1555 individuals. Findings: Other than three small randomized controlled studies, the data consisted of small series and case reports. CDI was the most common indication for FMT ( N  = 1190), with the majority of the remaining cases receiving FMT for inflammatory bowel disease. FMT had also been applied for irritable bowel syndrome, metabolic syndrome and constipation in small numbers. Adverse events appear to be uncommon, often mild and self-limiting; however, serious adverse events including bacteraemia, perforations and death have been reported. Conclusion: The vast majority of adverse events of FMT appear to be mild, self-limiting and gastrointestinal in nature. In some cases, a credible association was not established due to the lack of controlled data. There is a need for standardized, randomized controlled trials to qualify and quantify the risks associated with FMT.